The Status of Evidence-Based Dentistry in Iran - N Navabi; A Shahravan; SMR Khoshroo; L Asadi (Islamic Azad University, 2016)
Evidence-Based Dentistry (EBD) is very limitedly known in Iran, and has been defined as an approach to oral healthcare that requires the judicious integration of systemic assessments of clinically relevant scientific evidences, related to patient's history and oral and medical conditions, with dentist's clinical expertise and patient's treatment needs and preferences. (1-5) The EBD is a popular medical field worldwide, involving the utilization of the results of clinical dental research that improves decision-making procedures to render the best treatment available to patients, determining the highest-quality treatment methods. (6, 7)